PENGARUH MEDIA PAPAN FLANEL TERHADAP KOGNITIF SISWA KELAS V SD NEGERI 3 PEUKAN PIDIE - Junaidah (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2025)
This study aims to determine the effect of flannel board media on the cognitive abilities of 5th grade students of SD Negeri 3 Peukan Pidie. The research design used by the researcher is an experimental research type with a pre-experimental one group pretest-posttest research design. The population in this study amounted to 175 people and the sample of this study was 30 of 5th grade students SD Negeri 3 Peukan Pidie consisting of 18 male students and 12 female students. Data collection techniques used were observation and tests. The results of the t-test where the significance level was 5% (0.05) obtained t-count 3.855> t-table 2.060. Thus, it can be concluded that there is an effect of flannel board media on students' cognitive abilities on 5th grade SD Negeri 3 Peukan Pidie.